2010
DOI: 10.17221/84/2009-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the structure, species composition and diversity of primary and harvested forests on Changbai Mountain, Northeast China

Abstract: Broadleaved-Korean pine (Pinus koraiensis) mixed forest is a typical vegetation type in the eastern Eurasian continent. We compared the structure, composition and diversity of a primary forest and a logged forest for effective management and regeneration of a mixed forest ecosystem on Changbai Mountain, Northeast China. The logged forest was subjected to selective harvesting twenty years ago. The mean diameter and basal area for overall trees (≥ 2 cm dbh) were higher in the primary forest than in the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…Our results suggest diversity, in general, is not much different between the logged and reserve stands; in fact, canopy tree richness may increase after timber harvesting. While a number of studies have shown positive effects on species richness following selective logging (Berry et al, 2008;Swaine and Agyeman, 2008;Su et al, 2010), others have shown decreases (Huang et al, 2003;Felton et al, 2006;Gradstein et al, 2007;Farwig et al, 2008), suggesting that factors other than harvesting may be influencing measures of diversity across these forest types (Clark and Covey, 2012). While it is difficult to be certain based on the available data, the increase in richness observed here is possibly the result of the release of shade-tolerant understory species (e.g.…”
Section: Tree Species Diversitymentioning
confidence: 64%
“…Our results suggest diversity, in general, is not much different between the logged and reserve stands; in fact, canopy tree richness may increase after timber harvesting. While a number of studies have shown positive effects on species richness following selective logging (Berry et al, 2008;Swaine and Agyeman, 2008;Su et al, 2010), others have shown decreases (Huang et al, 2003;Felton et al, 2006;Gradstein et al, 2007;Farwig et al, 2008), suggesting that factors other than harvesting may be influencing measures of diversity across these forest types (Clark and Covey, 2012). While it is difficult to be certain based on the available data, the increase in richness observed here is possibly the result of the release of shade-tolerant understory species (e.g.…”
Section: Tree Species Diversitymentioning
confidence: 64%
“…The infrastructure developed to facilitate logging access often makes areas more accessible following logging, dramatically increasing the likelihood of chronic anthropogenic disturbance (Coffin, 2007;Laurance et al, 2009). Kumar and Ram (2005) surmised that the chronic nature of human disturbance did not allow degraded systems time to recover pre-logging levels of richness; a finding echoed by other authors (Klanderud et al, 2010;Su et al, 2010) and well supported in the forestry literature (Halpern, 1995;Cannon et al, 1998;Singh, 1998).…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, even in a study that showed no impact on canopy tree richness, Farwig et al (2008) showed a significant reduction in the species richness of late successional seedlings; a finding that presents the potential for effects to be magnified in the future. While most authors did not specifically characterize seedling richness, many also found a shift in tree community composition towards early successional species (Kumar and Ram, 2005;Aubad et al, 2008;Swaine and Agyeman, 2008;Klanderud et al, 2010;Su et al, 2010). These findings suggest that shifts in resource availability generally favor early successional tree species following harvest, and can lead to the exclusion of some sensitive late successional species.…”
Section: Discussionmentioning
confidence: 99%
“…Stand structure assists to understand forest ecosystems and biodiversity (Su et al 2010). Assessment of the composition, structure and regeneration status of species is required to ascertain the successful conservation and management of forest resources (Teketay 2005;Mishra et al 2013).…”
Section: Introductionmentioning
confidence: 99%